491 Usability and Acceptability of Clinical Decision Support for Children with Mild Traumatic Brain Injuries and Intracranial Injuries: A Mixed Methods Study. (1st April 2022) - Greenberg, Jacob K.; Otun, Ayodamola; Carpenter, Christopher; Brownson, Ross; Kuppermann, Nathan; Limbrick, David D.; Foraker, Randi; Yen, Po-Yin
Abstract : INTRODUCTION: Electronic clinical decision support (CDS) may improve the safe, evidence-based management of children with mild traumatic brain injuries (mTBI) and intracranial injuries. METHODS: Emergency medicine and neurosurgery physicians were recruited to participate in study sessions to test the usability and acceptability of a novel CDS prototype in a simulated electronic health record environment. Testing sessions included interacting with the tool using three simulated clinical cases (https://head-injury-risk-predictor.web.app/case-1.htmlt ), a think-aloud protocol, an acceptability and usability survey, and a semi-structured interview. The prototype was updated twice during testing (phases 1-3) to reflect user feedback. Usability problems were categorized and quantified using content analysis and reported with a descriptive summary. The semi-structured interviews were analyzed using thematic analysis. RESULTS: Twenty physicians (10 each from neurosurgery and emergency medicine) were recruited from nine separate hospitals. Most participants worked at teaching hospitals (80%) and level 1 trauma centers (75%). During the prototype updates, problems with clarity of terminology and wording were identified and corrected, along with problems navigating through and using the CDS interface. Corresponding to these changes, the number of usability problems dropped from 35 in phase 1 to 8 in phase 3, and the number of mistakes made went from 18 in phase 1 to 2 in phase 3. Through the survey, most participants found the tool easy to use (90%), useful for determining a patient's level of care (95%), and likely to improve resource use (90%) and patient safety (79%). Major interview themes related to the CDS's ability to support evidence-based decision-making and improve clinical workflow, proposed implementation strategies, and potential pitfalls to avoid. CONCLUSION: After the iterative evaluation and refinement, the elctronic CDS tool was found to be highly usable and useful for aiding the management of children with mTBI and intracranial injuries.